A Systematic Review of the Zinc Concentrations in the Prostate Fluid of Normal and Inflamed Gland - Zaichick, Vladimir; Zaichick, Sofia (International Journal of Innovative Research in Medical Science, 2019)
Background and objective: the prostate gland is subject to various disorders and of them chronic prostatitis (CP) is a complex disease. Various studies indicate some discrepancies regarding zinc (Zn) levels in prostatic fluid of normal and inflamed glands. The present study evaluated by systematic analysis the published data for Zn levels analyzed in expressed prostatic fluid (EPF) of normal and inflamed glands. Methods: The present systematic analysis included 25 studies, all of which were published in the years from 1961 to 2018 and selected by searching the databases Scopus, PubMed, MEDLINE, ELSEVIER-EMBASE, Cochrane Library, and the Web of Science. The articles were analyzed and “Median of Means” and “Range of Means” were used to examine heterogeneity of Zn concentrations in two groups of subjects – apparently healthy men “N” and patients with prostatitis “P”. Moreover, using the ratios of prostatic fluid Zn in “P” group to prostatic fluid Zn in “N” group (ZnP/ZnN) obtained (or calculated by us) in the reviewed studies, “Median of Means” and “Range of Means” for these ratios were found. The objective analysis was performed on data from the 25 studies, with total 285 subjects in “P” group and more than 900 subjects in “N” group. Results: The range of means of Zn concentration reported in the literature for normal EPF varies widely from 47.1 mg/L to 825 mg/L with median of means 501 mg/L. The range of means of Zn concentration for EPF of untreated prostatitis varies also widely from 56 mg/L to 491 mg/L, with median of means 268 mg/L. Thus, the obtained median of means for Zn concentration in normal human prostatic fluid is about two times higher than median of mean values of the element content in EPF of inflamed prostate. In other words, the analysis of 25 studies with discordant data regarding prostatic fluid concentration of Zn demonstrated that there is a significantly diminished concentration of Zn in EPF of patients with prostatitis compared to controls. Conclusion: There is a significant relationship between lowered Zn concentrations in prostatic fluid and prostatitis, but because of small sample size and high data heterogeneity, we recommend other primary studies.